ANALISIS KEBIJAKAN PEMERINTAHAN DONALD TRUMP TERHADAP PERBATASAN AMERIKA SERIKAT-MEKSIKO DALAM PERSPEKTIF KEAMANAN NASIONAL - Agussalim Burhanuddin; Muslimin, Maulida Zahrani Putri (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2024)
The issue of immigrants and borders is something that the United States is still trying to overcome in the context of a country that is the target of many individuals from other countries. Mexico is one of the contributors to the number of immigrants in the United States, especially with the direct border conditions between the two countries. This research then tries to see how Donald Trump's policy towards the United States-Mexico border, which brings a lot of insecurity to the United States. The method used in this research is a qualitative method. Fundamentally, it can be seen that the form of policy taken by Donald Trump is part of national defense in protecting the sustainability of the country and its people.